Remote sensing applications for rice mapping and yield estimation in the Senegal River Valley (SRV) of Senegal - Mathieu, Renaud; Murugesan, Deiveegan; Quicho, Emma; Faye, Omar Ndaw; Sall, Moussa; Gatti, Luca; Holec, Francesco (CGIAR Research Initiative on Digital Innovation, 2024)
Rice is a vital and staple food in Senegal, as it is for the whole of West Africa, and yet cultivation is still limited while consumption is continuously increasing. Rice mainly grows in the Senegal River Valley (SRV) (northern part) in highly intensive systems under irrigated conditions and in Casamance region (southern part) mainly under rainfed systems. Despite rice having a crucial role to play in the nation’s economy, culture and food security, Senegal has for many years imported most of the rice it consumes. To achieve the goal of self-sufficiency and encourage economic growth, Senegal is taking many interventions to improve their rice production while monitoring rice area and production estimates is crucial for designing/targeting interventions and for making sound policy decisions. This initiative aims to develop a digital rice monitoring platform in Senegal based on near-real-time satellite data to support national policies, food security, and market management, as well as to facilitate farmers’ resilience through the development of insurance and microfinance products. This report presents the preliminary results of mapping rice areas across the Senegal River Valley during dry and wet seasons of 2023 using the Remote sensing-based Information and Insurance for Crops in emerging Economies (RIICE) platform in collaboration with sarmap, Switzerland, the Institut Sénégalais de Recherches Agricoles (ISRA), and local partners.